The Struggle for Rights at Work: The United Electrical Workers, Contract Enforcement, and the Limits of Grievance Arbitration at Canadian General Electric and Westinghouse Canada, 1940s to 1960s - Taylor, Jeffery (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2019)
For decades Canadian trade unionists have expressed frustration with the grievance arbitration system, but this tends to be limited to criticisms of the legalistic nature of the process and the costs and delays involved in getting a judgement. There is little discussion or debate about the denial of the right to strike, which is the central feature of the system. Nor is there much discussion about approaches to contract enforcement that situate legal strategies in broader political strategies to use worker power effectively, including the withdrawal of labour. This study investigates how the United Electrical Workers (ue), a left-led union, defended workers’ rights at Canadian General Electric (cge) and Westinghouse in the early years of the new legal regime. Specifically, it charts the North American origins of grievance arbitration systems, sketches the development of personnel policies in the electrical industry, surveys the ue Canadian district’s struggle to establish contractual relations and codify workplace rights at these two corporations, reconstructs the elements of ue’s approach to contract enforcement, and reviews a number of mid-contract work stoppages at cge and Westinghouse between 1946 and 1966 to determine how the union, workers, employers, and arbitrators negotiated the ban on grievance strikes as they adjusted to new legislation and new collective agreement language.